2003
DOI: 10.1099/ijs.0.02342-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbulbifer salipaludis sp. nov., a moderate halophile isolated from a Korean salt marsh

Abstract: Department of Food and Life Science, Sungkyunkwan University, Chunchun-dong 300, Jangan-gu, Suwon, Korea A Gram-negative, non-motile, non-spore-forming, moderately halophilic rod (strain SM-1 T ) was isolated from salt marsh around the junction of the Youngsan River and the Yellow Sea in Korea and subjected to a polyphasic taxonomic study. This organism grew optimally at 37˚C and was able to grow at 10 and 45˚C. It grew optimally in the presence of 2-3 % (w/v) NaCl. The major fatty acids in strain SM-1 T were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
57
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 168 publications
(58 citation statements)
references
References 24 publications
(18 reference statements)
0
57
0
Order By: Relevance
“…A single species, Microbulbifer hydrolyticus, was included within this genus. The second species of the genus Microbulbifer was Microbulbifer salipaludis, which was proposed recently by Yoon et al (2003b). Phylogenetic analyses based on 16S rDNA sequences have shown that the two Microbulbifer species fall within the c-subclass of the Proteobacteria (González et al, 1997; Solano & Sanchez-Amat, 1999;Anzai et al, 2000;Yoon et al, 2003b).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…A single species, Microbulbifer hydrolyticus, was included within this genus. The second species of the genus Microbulbifer was Microbulbifer salipaludis, which was proposed recently by Yoon et al (2003b). Phylogenetic analyses based on 16S rDNA sequences have shown that the two Microbulbifer species fall within the c-subclass of the Proteobacteria (González et al, 1997; Solano & Sanchez-Amat, 1999;Anzai et al, 2000;Yoon et al, 2003b).…”
mentioning
confidence: 97%
“…The second species of the genus Microbulbifer was Microbulbifer salipaludis, which was proposed recently by Yoon et al (2003b). Phylogenetic analyses based on 16S rDNA sequences have shown that the two Microbulbifer species fall within the c-subclass of the Proteobacteria (González et al, 1997; Solano & Sanchez-Amat, 1999;Anzai et al, 2000;Yoon et al, 2003b). Chemical markers of this genus include the presence of a major amount of iso-C 15 : 0 and ubiquinone with eight isoprene units (Q-8) (González et al, 1997;Yoon et al, 2003b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 16S rRNA gene was amplified by PCR as described previously (Yoon et al, 1998) using two universal primers, 9F (5¢-GAGTTTGATCCTGGCTCAG-3¢) and 1512R (5¢-ACGGTTACCTTGTTACGACTT-3¢). Sequencing of the amplified 16S rRNA gene and phylogenetic analysis were performed as described by Yoon et al (2003). DNA-DNA hybridization was performed fluorometrically by the method of Ezaki et al (1989) using photobiotinlabelled DNA probes in microdilution wells.…”
mentioning
confidence: 99%
“…Sequencing of the amplified 16S rRNA gene and phylogenetic analysis were performed as described by Yoon et al (2003). DNA-DNA hybridization was performed fluorometrically by the method of Ezaki et al (1989) using photobiotin-labelled DNA probes and microdilution wells.…”
mentioning
confidence: 99%